Circulatory microRNA-145 expression is increased in cerebral ischemia - Gan, C.S.; Wang, C.W.; Tan, K.S. (2012)
Cerebral ischemia or ischemic stroke is mainly attributed to vascular and circulation disorders. Among protein biomarkers, RNA profiles have also been identified as markers of ischemic stroke. MicroRNA-145 expression is ostensibly recognized as marker and modulator of vascular smooth muscle cell phenotype; however, expression levels in ischemic stroke had not been investigated. Employing real-time quantitative PCR, we examined the expression profile of circulatory microRNA-145 in healthy control subjects (N = 14) and ischemic stroke patients (N = 32). Circulatory microRNA-145 expression was significantly higher in ischemic stroke patients than in control subjects. This demonstrates that hemostatic mechanisms are affected by ischemic stroke. We conclude that circulating microRNA-145 has potential as a biomarker for ischemic stroke.